Factors Influencing the Incidence of Neonatal Sepsis In the Neonatal Intensive Care Unit, Budhi Asih Regional Hospital - Nuhan, Helena Golang; Mirawati (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Neonatal sepsis remains a major health problem in Indonesia, with a prevalence of 8–15% in referral hospitals and contributing to the second leading cause of infant mortality after asphyxia (Ministry of Health of the Republic of Indonesia, 2022). Risk factors influencing the incidence of neonatal sepsis include prematurity, low birth weight (LBW), gender, and invasive procedures. At Budhi Asih Regional Hospital, Jakarta, the incidence of neonatal sepsis in 2024 was recorded at 46.69% of 272 NICU patients. Therefore, this study was conducted to determine the factors influencing the incidence of neonatal sepsis in the NICU of Budhi Asih Regional Hospital, Jakarta. This study used a quantitative cross-sectional design. The study population was all infants treated in the NICU of Budhi Asih Regional Hospital from January to December 2024. A sample of 80 infants was selected using a purposive sampling technique. The independent variables were gestational age, gender, birth weight, and invasive procedures, while the dependent variable was the incidence of neonatal sepsis. The research instrument was medical record data analyzed using the Chi-square test at a 95% confidence level. Gestational Age: Infants with gestational age <37 weeks experienced more neonatal sepsis than full-term infants (p<0.05). Low Birth Weight (<2500 gr) was significantly associated with the incidence of neonatal sepsis (p<0.05). Gender: There was no significant association between gender and the incidence of neonatal sepsis (p>0.05). Invasive Procedures: Infants who underwent invasive procedures were at higher risk of neonatal sepsis (p<0.05). Factors associated with the incidence of neonatal sepsis in the NICU of Budhi Asih Hospital, Jakarta were gestational age, low birth weight, and invasive procedures. Gender was not associated with the incidence of neonatal sepsis. Prevention of neonatal sepsis needs to be focused on close monitoring of premature infants, LBW, and infection control related to invasive procedures in the NICU.